2007
DOI: 10.1002/bjs.5836
|View full text |Cite
|
Sign up to set email alerts
|

Portal vein embolization before major hepatectomy and its effects on regeneration, resectability and outcome

Abstract: DH contributes prognostic information additional to that gained by volumetric evaluation in patients undergoing PVE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
315
7
12

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 435 publications
(347 citation statements)
references
References 42 publications
9
315
7
12
Order By: Relevance
“…In 2004, Dindo et al proposed a modification that included a new five-grade classification system with the possibility of combining grades; ''disability'' was added to the system, ''hospital stay'' was eliminated as a complication and ''organ failure'' was changed to carry more weight in grading [12]. The so-called ''Clavien-Dindo'' classification has been adapted for use in general surgery [10] and for other surgical subspecialties such as gastroenterology/hepatology [3,11,17,[22][23][24][25]28], urology [19], and nephrology [18,27]. Given this system appears useful for general surgery and other specialties, we explored its use in orthopaedic surgery.…”
Section: Introductionmentioning
confidence: 99%
“…In 2004, Dindo et al proposed a modification that included a new five-grade classification system with the possibility of combining grades; ''disability'' was added to the system, ''hospital stay'' was eliminated as a complication and ''organ failure'' was changed to carry more weight in grading [12]. The so-called ''Clavien-Dindo'' classification has been adapted for use in general surgery [10] and for other surgical subspecialties such as gastroenterology/hepatology [3,11,17,[22][23][24][25]28], urology [19], and nephrology [18,27]. Given this system appears useful for general surgery and other specialties, we explored its use in orthopaedic surgery.…”
Section: Introductionmentioning
confidence: 99%
“…[10,[28][29][30] Liver volume assessed 3-4 weeks post portal vein embolisation shows an increase in volume of 5% being associated with improved patient outcomes. [8] Lewis et al 2006 [10] found liver volume reduced by 14% over a six week period following the implementation of a low calorie diet. Edholm et al 2014 [28] showed an average decrease in liver size of 18% in ten female participants following two weeks on a low calorie diet.…”
Section: Discussionmentioning
confidence: 99%
“…An increase in size of 5% is associated with improved patient outcomes. [8] In addition to this, liver volume calculations are commonly used to estimate drainage volume prior to endoscopic biliary drainage. [9] Liver volume is also commonly assessed six weeks and one week prior to gastric banding surgery to ensure adequate volume reduction.…”
Section: Introductionmentioning
confidence: 99%
“…As such, an absolute percentage point increase of >5 % is associated with significant reduction in the risk of PHI and death. 23 Frequently, patients with extensive liver disease require two-stage hepatectomy. Combined with perioperative chemotherapy, two-stage hepatectomy +/− PVE can result in prolonged 5-year OS of 51 %.…”
Section: Metachronous Presentation Of Extensive (Multifocal and Bilatmentioning
confidence: 99%